2014
DOI: 10.1364/oe.22.022561
|View full text |Cite
|
Sign up to set email alerts
|

Determination of collagen fiber orientation in histological slides using Mueller microscopy and validation by second harmonic generation imaging

Abstract: We studied the azimuthal orientations of collagen fibers in histological slides of uterine cervical tissue by two different microscopy techniques, namely Mueller polarimetry (MP) and Second Harmonic Generation (SHG). SHG provides direct visualization of the fibers with high specificity, which orientations is then obtained by suitable image processing. MP provides images of retardation (among other polarimetric parameters) due to the optical anisotropy of the fibers, which is enhanced by Picrosirius Red stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…Collagen fibers orientation have been studied on ex vivo uterine cervial tissue with SHG [43] and breast tumor tissue with polarization-resolved SHG [44]. Tanaka et al found that skin burn tissue presents molten and fibrous structures of dermal collagen [41], which is consistent with our finding on Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Collagen fibers orientation have been studied on ex vivo uterine cervial tissue with SHG [43] and breast tumor tissue with polarization-resolved SHG [44]. Tanaka et al found that skin burn tissue presents molten and fibrous structures of dermal collagen [41], which is consistent with our finding on Fig.…”
Section: Discussionsupporting
confidence: 91%
“…6(h). The strong Retardance observed in the zones around the malpighian epithelium has been attributed to the signature of a well-ordered collagen layer composing the subepithelial connective tissue 13 . Otherwise, the polyp does not show a well-defined inner organization in the subepthelial connective tissue, which results in low Retardance values as well as erratic Azimuth orientations, as can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of tissue anisotropy modification enables one to differentiate between high-grade cervical dysplasia and healthy squamous epithelium with an averaged value of both sensitivity and specificity of about 80% at a wavelength of 550 nm. The intense anisotropy observed in healthy squamous epithelium was interpreted as the signature of the structured and ordered collagen that forms the connective tissue beneath the healthy epithelium itself 13 . A pre-cancerous evolution in the epithelium can degrade the structure of said collagen fibers in the nearby connective tissue 17 , with the consequence of decrease in its macroscopically measurable anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has also been shown that the optical properties of turbid tissue, including the reduced scattering coefficient, can be determined from diffusely scattered polarized light. 3 The incorporation of polarimetric imaging in more conventional techniques such as microscopy or optical coherence tomography helps in the extraction of precise information such as on collagenous tissue structure (eye, 4 skin, 5 and cervix 6 ). Promising studies of polarimetric examination of tissues were carried out in dermatology, [7][8][9][10][11][12][13] where melanomas or other lesions (lupus) were characterized by various polarimetric indicators (depolarization and birefringence).…”
Section: Introductionmentioning
confidence: 99%